2022
DOI: 10.3389/fcvm.2021.794834
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Using Second-Generation Cryoballoon and Radiofrequency Catheter for Atrial Fibrillation Ablation in Patients With the Common Ostium of Inferior Pulmonary Veins

Abstract: Aims: To compare the procedural outcomes of cryoballoon ablation (CBA) and radiofrequency ablation (RFA) in atrial fibrillation (AF) patients with the common ostium of inferior pulmonary veins (COIPV) and to explore the effect of COIPV on CBA performance through the assessment of anatomical factors.Methods: A total of 18 AF patients with COIPV were included. Pulmonary vein isolation (PVI) was performed with second-generation CBA or RFA. The anatomical characteristics of COIPV and procedural outcomes were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…It is rare but challenging for PVI ablation ( 28 , 29 ). Yu et al ( 28 ) used the “tri-circle” strategy to finish the circumferential PV isolation, and Li et al ( 30 ) used the second-generation cryoballoon at the ostium of the left and right inferior pulmonary veins. The above methods inevitably increase the ablation dosing of LAPW.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare but challenging for PVI ablation ( 28 , 29 ). Yu et al ( 28 ) used the “tri-circle” strategy to finish the circumferential PV isolation, and Li et al ( 30 ) used the second-generation cryoballoon at the ostium of the left and right inferior pulmonary veins. The above methods inevitably increase the ablation dosing of LAPW.…”
Section: Discussionmentioning
confidence: 99%
“…CIPT is a rare variant affecting less than 1% of patients undergoing ablation for atrial fibrillation [ 1 , 2 ]. In such patients, both inferior pulmonary veins drain via a common trunk.…”
mentioning
confidence: 99%
“…Consequently, the esophagus is in contact inferiorly, posteriorly, and superiorly with CIPT. Hence, ablation with thermal energy exposes such patients to an increased risk of atrioesophageal fistula [ 1 ]. Because of the higher risk of fistula, some authors have elected to not isolate the CIPT when found during a radiofrequency pulmonary vein isolation procedure [ 2 ].…”
mentioning
confidence: 99%